2010
DOI: 10.1007/s12011-010-8674-5
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite-Induced Apoptosis Is Prevented by Selenite in A375 Cell Line

Abstract: Arsenic trioxide induces apoptosis and clinical remission in patients diagnosed with acute promyelocytic leukemia. The human malignant melanoma A375 cells were treated with NaAsO2 (0.1–130 μM) and also treated with combined 10 μM NaAsO2 and 10 μM Na2SeO3. NaAsO2 arrested cell growth in the G1 phase and induced apoptosis in a concentration- and time-dependent manner. In contrast, administration of Na2SeO3 antagonized the cell growth inhibition and apoptosis induced by NaAsO2. The NaAsO2 treatment resulted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The results showed that sodium selenite 3 mg/kg body weight protected the rat liver against sodium arsenite 5.55 mg/kg body weight-induced pro-oxidant effects such as lipid peroxidation, a decreased level of GSH, and reduced GPx activity. Treatment with 10 mM ($1.73 mg/L) of sodium selenium after the 10 mM ($1.299 mg/L) of sodium arsenite exposure effectively protected A375 cells against arseniteinduced cell death [16]. The cytotoxicity induced by 2.5 mM ($0.324 mg/L) of sodium arsenite was partially abated in the presence of 4 mM ($0.691 mg/L) of sodium selenite in human osteosarcoma (TE 85) cells [24].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results showed that sodium selenite 3 mg/kg body weight protected the rat liver against sodium arsenite 5.55 mg/kg body weight-induced pro-oxidant effects such as lipid peroxidation, a decreased level of GSH, and reduced GPx activity. Treatment with 10 mM ($1.73 mg/L) of sodium selenium after the 10 mM ($1.299 mg/L) of sodium arsenite exposure effectively protected A375 cells against arseniteinduced cell death [16]. The cytotoxicity induced by 2.5 mM ($0.324 mg/L) of sodium arsenite was partially abated in the presence of 4 mM ($0.691 mg/L) of sodium selenite in human osteosarcoma (TE 85) cells [24].…”
Section: Discussionmentioning
confidence: 97%
“…The metabolic roles of selenium in mammalian cells are due to its function in the active site of many antioxidant enzymes, especially the key enzyme, selenium-dependent glutathione peroxidase (GPx) [12]. At the cellular level, the protective effects of selenium on arsenic toxicity have been described in cultured human leukemia HI-I-60 cells [14], human hepatocytes [15], and the A375 cell line [16]. At the cellular level, the protective effects of selenium on arsenic toxicity have been described in cultured human leukemia HI-I-60 cells [14], human hepatocytes [15], and the A375 cell line [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first proof of the As/Se interaction in relation to cancer was found in mice [30] and rats [31], when As III antagonized the carcinogenic effect of Se IV . Later, studies with human malignant melanoma cells demonstrated that arsenite-induced apoptosis is prevented by selenite [32]. A Human cells As-induced apoptosis is prevented by Se [32] A Mice As prevents carcinogenic effect of Se [30] A Rats As prevents carcinogenic effect of Se [31] A Rats As protects against the toxicity of Se (growth, mortality rate, pathological condition of the liver) [20,33,186] A Rats As induces mucosal glutathione synthesis, explaining its protective effect against Se [187] A Dogs As antagonizes Se-induced subnormal growth and restricted food intake [35] A Cattle As protects against Se toxicity [36] A Hogs As protects against Se toxicity [ Se prolongs the half-lives of Hg-exposed animals [190] A Rats Se changes the subcellular Hg distribution [191] S Oysters High levels of Se increase Hg toxicity [192] SeO 3 2− /MeHg + A Chickens Se changes the subcellular and pattern distribution of Hg [193] A Medaka fish Se protects against Hg-induced histopathological changes [151] SeO 2 /Hg 2+ A Chicks Se toxicity is decreased by Hg [194] SeO 4 2− /MeHg + A Mice Se protects against Hg-induced neurotoxicity [63] Protective effects of arsenic in rats [19,20,23,33,34], dogs [35], cattle [36], mice [37], hogs [38], steers [39], mallards [40] and poultry [41][42][43] have been observed/proposed.…”
Section: Arsenic and Seleniummentioning
confidence: 99%
“…In the context of proapoptotic execution, one of the key mechanisms was established with an apoptotic effect via the opening of the mPTP [ 167 ]. Arsenic trioxide was also considered as an agent disrupting mitochondrial membrane potential, and the proapoptotic effect triggered by arsenic trioxide could also be due to its ability to inhibit Bcl-2 [ 168 ]. Likewise, Lonidamine (LND) was developed as an indazole carboxylate and has been investigated to target ANT to induce mitochondria-mediated apoptotic cell death [ 169 ] ( Figure 4 ).…”
Section: Pharmacological Switches Of Mptp Opening/closing In Cancer T...mentioning
confidence: 99%